The conceptual assessment of Malaysian entrepreneurship environment and EO economic contribution - Othman, Masayu; Saud, Mohammad Basir; Mat Isa, Mohd Azwardi; Abdullah, Nabaz Nawzad (IISTE, 2016)
Entrepreneurial orientation (EO) is a strategy of the organization that increasingly changes the outcome of their performances.This study intended to examine the economic outcome of the entrepreneurial orientation.It also tried to explain how government and the perceived environment impacts on the business organizations to successfully applying EO dimensions.The study found that applying EO in the business organizations less contributed to the economic growth of Malaysia comparing to other countries. The study also found that Malaysian government and private institution offered supportive programs to transfer the attitude and traits of the firms towards the application of the EO.The repayment of the loans is found to be an issue to government and private institutions to maintain their supports.The perceived environment, entrepreneurial knowledge and the attitude of entrepreneurs are key factor of the successful application of EO dimensions.